The Early and Late Greek Immigrant: a Comparative Sociological and Socio-Psychological Profile - Kourvetaris, George (Études helléniques / Hellenic Studies, 1983)
In attempting a social and social-psychological profile of the early and the late Greek immigrants in the United States, this analysis describes and discusses a number of differences and similarities that characterize the two groups. Briefly, the overall background and the life in the new country of these two Greek groups in America are presented, and the author enlists a number of characteristics as a way of comparing the two groups. In concluding, the author notes that the observed differences between the early and the late Greek-Americans may be better explainedin the context of continuous changes and modernization of the U.S. society over the years than due to deep-rooted (esoteric) differences between the two groups, groups which are made up from the same “cloth”, as the author himself notes.